Comparison of the Catalytic Activity of Carbon, Spinel-Based, and Carbide Materials in the Na-Air Battery - Faktorovich-Simon, Evelina; Natan, Amir; Peled, Emanuel; Golodnitsky, Diana (Frontiers in Materials, 2019)
Rechargeable sodium-oxygen batteries have attracted much interest in recent years, owing to their high theoretical specific energy, and the abundance of sodium. The material of which the cathode is constructed influences the performance of the battery. In this study, we show that low-surface-area glassy carbon (GC) cannot operate for more than four consecutive cycles, whereas high-surface-area carbon materials, such as Black Pearl 2000 carbon (BP 2000), significantly increase the number of cyclic- voltammetry runs, without current reduction. NiCo2O4 was previously considered a promising material for the cathode. However, its activity was not compared with the only carbon-based electrode. Here we compare the electrochemical performance of four different NixCoyOz powders to BP 2000, XC72R, and SB carbon. The highest activity was obtained with the use of a powder, which contained 45% NiCo2O4, 10% CoO, 30% metallic nickel, and 15% metallic cobalt. We believe that the metallic nickel and cobalt phases are responsible for this high catalytic activity. Accelerated stress tests of XC72R, BP 2000, SB, and TiC powders, after 100 cyclic-voltammetry cycles, revealed that TiC exhibited the greatest loss of reduction peak area ( 57%) during the test, indicating the highest loss of catalytic activity. It also exhibited higher loss of oxidation peak area than Vulcan XC72R ( 68% vs. 35%), but lower than BP 2000 ( 90%) and SB carbon ( 72%). The reason for such a high degradation probably comes from strong surface changes or loss of adhesion of the catalyst powder to the GC electrode during the AST. It was suggested that in most cases, it is the OER process, which exhibits stronger deterioration.